Optimum Design of a Renewable-Based Integrated Energy System in Autonomous Mode for a Remote Hilly Location in Northeastern India - Chakraborty, Samrat; Mukherjee, Debottam; Guchhait, Pabitra Kumar; Bhattacharjee, Somudeep; Abdelaziz, Almoataz Youssef; El-Shahat, Adel (MDPI, 2023)
Integration of a grid with an under-developed remote hilly area faces various technical and geographical challenges. Thus, generation of power from renewable resources in off-grid conditions has become one of the most cost-effective and reliable solutions for such areas. The present research deals with the possible application of an integrated solar/hydro/biomass/battery-based system to generate power in autonomous mode for a remote hilly town of a northeastern Indian state. Four different cases of the integrated energy system (IES) were designed using the hybrid optimization model for electric renewable (HOMER Pro), examining the performance of each case. The best combination of the integrated system was chosen out of several cases depending upon the optimized solution that can meet the load demand of the proposed hilly town sustainably, reliably and continuously. The simulation results show that the integrated battery/biomass/hydro/solar-based system is the best optimized, cheapest and most suitable solution to generate renewable-based power for the specified location, having the lowest net present cost (NPC) of USD 644,183.70 with a levelized cost of energy (COE) of 0.1282 USD/kWh. Further, the result also indicates that the optimized configuration reduces the emission of CO2 gas in the environment compared to the battery/biomass/hydro system having the worst emission rate. A sensitivity study was also carried out with variation in load, hydro stream flow and solar irradiation, respectively that may largely affect the technical as well as economical aspect of an integrated energy system.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: biomass system; cost of energy; HOMER Pro software; hydro power; integrated energy system; net present cost; sensitivity analysis; solar PV; techno-economic analysis